Prosthetic rehabilitation of a young patient with dentinogenesis imperfecta and hemophilia A - Laura Lipták; Klaudia Lipták; Gergely Balaton; Noémi Katinka Rózsa (Hungarian Dental Association, 2023)
Introduction: Dentinogenesis imperfecta (DI) is a genetic disease that affects the dentin of the teeth. The autosomal dominantly inherited disease affects only the tissues of connective tissue (mesodermal) origin of the teeth, so there are no changes in the enamel and the periodontium. Due to poor quality dentin, the teeth become discolored and the enamel easily peels off. In the dental treatment of patients with DI, the focus should be on indirect restorations as soon as possible, so the dentist must diagnose the condition as early as possible so that the possibility of early intervention is realized, as well as balancing the decision for early intervention with the long-term survival of the restorations. Case report: A 15-year-old young male patient came to the Department of Paediatric Dentistry and Orthodontics of Semmelweis University, to have the veneers on his lower incisors replaced. He also wanted a comprehensive aesthetic rehabilitation. The anamnesis revealed that the patient's father also suffers from DI, and the patient lives with hemophilia A. Based and the literature evidence and recommendations, we planned indirect restorations. The decreased occlusal vertical dimension was increased; in the first phase to adapt the neuromuscular system to the increased vertical dimension, polymethyl-methacrylate (PMMA) restorations were prepared. After the patient both aesthetically and functionally having been satisfied with the temporary restorations, the final restoration were planned as a monolithic zirconia crowns and splints for the upper and lower arches. For the cementation resin modified glass ionomer was used to avoid the adhesive technique, which is not recommended in such cases. The prosthodontic phase was preceded by professional oral hygiene treatment, instruction, and motivation. Summary: For patients with DI, the key is the early diagnosis and its treatment is essential. Scientific evidence indicates that indirect restorations should be preferred over direct ones in patients with DI. Close cooperation with the hematologist is necessary during the treatment of the patient with hemophilia A.